Der bioliq®‐Flugstromvergaser – ein Baustein der Energiewende. Issue 1 (17th January 2018) - Eberhard, Mark; Santo, Ulrike; Böning, David; Schmid, Hannah; Michelfelder, Bernd; Zimmerlin, Bernd; Günther, Armin; Weigand, Peter; Müller‐Hagedorn, Matthias; Stapf, Dieter; Kolb, Thomas
Abstract: The bioliq® process was developed at the Karlsruher Institute for Technology (KIT) for the generation of synthetic fuels out of residual biomass. This multiple step process not only considers the necessity for decentralized of the biomass but also the necessity for a large centralized fuel synthesis, which benefits from economy of scale. The entire chain is tested and operated in the pilot plant at KIT. The high pressure entrained‐flow gasifier, from Air Liquide Global E&C Solutions, converts the biomass into a syngas, which is then processed into gasoline in the downstream synthesis steps. First experimental results from the plant are presented.